A nanofibrillar conjugated polymer film as an interface layer for high-performance CsPbIBr2 solar cells with efficiency exceeding 11%. Issue 11 (16th May 2022) - Wang, Qian; Xu, Yinyan; Zhang, Lun; Niu, Pujun; Zhou, Ru; Lyu, Mei; Zhang, Guobing; Lu, Hongbo; Zhu, Jun
Abstract : A self-assembled nanofibrillar conjugated polymer film is used to optimize the CsPbIBr2 /hole-transporting layer interface. The obtained CsPbIBr2 solar cell demonstrates an efficiency of 11.05% with excellent long-term stability. Abstract : The perovskite/hole-transporting layer interface plays a crucial role in the performance of perovskite solar cells. Herein, a conjugated polymer (CP) is employed as an interface layer in CsPbIBr2 solar cells. On top of the CsPbIBr2 layer, the CP self-assembled into a nanofibrillar film which shows multiple effects: optimization of the energy level alignment, enhancement of the hole extraction, passivation of the perovskite layer and reduction of the defect density. As a result, the power conversion efficiency of the corresponding CsPbIBr2 /CP device is improved to 11.05%, with a V OC of 1.19 V, a J SC of 12.69 mA cm −2, and a FF of 73.31%. Moreover, the device efficiency retains about 91% of its initial value for nearly 900 hours in air. This proposed CP-passivated interface strategy will open a new avenue for achieving high-performance inorganic perovskite solar cells.